The activation dilemma: reconciling the fairness and effectiveness of minimum income schemes in Europe - Moreira, Amilcar (Bristol, 2008)
"The activation of social welfare recipients has been, and still is, a central issue in the development of social and employment policies in Europe. This ambitious book explores the employment effectiveness of minimum income schemes, and provides the first comprehensive examination of its dependency on how the rights and obligations of the recipients are defined. The book argues that the right to a minimum income can only be adequately justified with reference to the individual's right to personal development. Combining political theory and policy analysis, the author draws on evidence from eight different European countries to illustrate how it is possible to combine higher levels of employment effectiveness with the respect for recipients' right to personal development. Exploring the balance between fairness and effectiveness in the activation of minimum income recipients and acknowledging that individuals have both rights and obligations, this book will provide a useful reference tool to students, researchers and policy-makers with an interest in the work versus welfare nexus."